Analisis Studi Kelayakan Bisnis Pada Usaha Cilok Goang Yummy - Agustin, Imel Aura; Rahman, Layalia Auliaur; Sampurna, Yoga; Perwito, Perwito (Jurnal Manajemen Akuntansi (JUMSI), 2025)
A business feasibility study is a series of evaluations used to assess the viability of a proposed investment or business. Cilok goang, one of West Java’s traditional foods, holds promising prospects for development into a potential business. This study aims to analyze the feasibility of the cilok goang business using a feasibility study approach encompassing seven main aspects: legal, market and marketing, financial, technical and operational, management and organization, economic and social, and environmental impact. The methods used include qualitative and quantitative approaches, with data collected through field observations, market surveys, and document analysis. The results indicate that the cilok goang business has broad market opportunities, supported by high demand, especially in urban areas. Financially, the business demonstrates favorable profit projections with a relatively short payback period. Operationally, raw materials are readily available at affordable prices, and the production process can be adapted to various scales. Legal and environmental aspects do not pose significant challenges. Therefore, the cilok goang business is deemed feasible for development, either by opening new branches or through product diversification.